Panic proof : the new holistic solution to end your anxiety forever - Cain, Nicole (Rodale, 2024)
"Panic Proof offers a holistic approach to dealing with panic disorders, amounting to a personalized path to freedom for the millions of people who have had panic attacks. While other books have focused on the thoughts that contribute to panic, Panic Proof is the first book to teach the body that it's safe in order to prevent panic before it attacks, with remedies ranging from probiotics, herbal remedies, and adaptogens targeted for your anxiety type to healing practices for releasing trauma stored in the body. In a warm and approachable style, Dr. Cain shares her personal story of managing panic, examples from the patients she's helped, and her science-based protocol derived from a decade of working with clients to manage their own panic disorders. Guiding you through the nine types of anxiety that Dr. Cain has identified, the book includes quizzes, worksheets, and self-reflection checklists to guide you along your journey to panic freedom"--